Derrida and the Structure of the ‘Messianic’ in the Specter of Marx - Joseph Nietlong (Program Studi Sosiologi, 2020)
This paper sets out to explore the motive behind Derrida’s usage of the messianic, a term so already charged with religious significance. The messianic is a term that has so much baggage of a certain dogmatic, particular, and exclusive way of reading and interpreting human history. Why does Derrida employ the term messianicity? To what degree had he been successful in his usage of it? What has been gained or lost therein? Another line of inquiry that this paper sets out to follow is to find the difference that marks Derrida’s messianic from (other) previous ones, for instance that which characterize the institutionalized Abrahamic religions: Judaism, Christianity, Islam, etc. and the sort of messianism that found expression in Marxism. Given the structure of Derridean Messianism, the paper attempt to see the relevant opening it could provide toward reading, de/re-constructing the cultural, socio-economic and political history of human kind. Derrida, though not one who believes in religion, this work shall attempt to show how he sets out in the Specter of Marx, to forge the link between Marx and some prophets, through the mediation of Shakespeare.